Dampak Rehabilitasi Lahan Terkena Tsunami dengan Cendawan Mikoriza Arbuskula (CMA) dan Pupuk Kandang Terhadap Ketersediaan P Tanah, Pertumbuhan dan Kandungan P Tanaman Jagung - Fikrinda Fikrinda; Zuraida Zuraida; Yusnizar Yusnizar; Marlina Marlina (Jurnal Agrista, 2007)
Impact of Land Rehabilitation by Arbuscule Mycorrhizae Fungi (AMF) and Organic Matter for Tsunami-Affected Land on the Availability of Soil P, Growth and P Uptake of MaizeABSTRACT. Phosphor, a macro element, is often a problem especially in tropical regions not only because its content in soil but also its availability. This problem also occurred at tsunami-affected land. Both micorrhizae and organic matter able to improve soil quality, include by improving nutrient status of soil. The aim of this work were to examine the effect of AM fungi and organic matter on availability of soil P and N and P uptake of maize at the tsunami-affected land. This work was arranged in Factorial Randomized Block Design with three replication. The results were both AMF inoculation and organic matter affected the availability of soil P not significantly. The dry weight of upper crop and P uptake of maize were influenced by interaction of these treatments high significantly while the dry weight of root was affected significantly.